Mathematical Modelling of Heat and Mass Transfer in a Roof Type Solar Distillation System (Nigerian Journal of Technology, 2021)
This research examined the performance of a roof type solar distillation system. A model was developed that captured the influence of the cover angle on still performance in terms of evaluating the heat transfer coefficient, yield and efficiency. The previous models of evaluating these matric has been shown to be unsatisfactory due to over prediction. The objectives are to clarify the misconception on the efficiency, to validate the derived expression for the Nusselt’s number of condensation under an inclined surface and to perform sensitivity analysis on the dimensionless parameters with derived models. The derived model has a practical significance because it provides much information on the dependence of the heat transfer coefficient on the cover angle. The model was solved with MATLAB, and results show a well correlated trends with the established work of literature and the proposed model having the lest efficiency as the model is without the over prediction inherent in other models due to non-inclusion of evaporation in the analysis of free convection of air. The peak yield of all the models occurs at about 11:00 AM, with the proposed model having a peak yield of about 0.045kg.http://dx.doi.org/10.4314/njt.v40i2.11